2012
DOI: 10.1007/s00167-012-2020-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical treatment for acute patellar dislocation with special emphasis on the MPFL injury patterns

Abstract: Therapeutic, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 30 publications
1
38
0
4
Order By: Relevance
“…3): the overlap region, which is proximal to the patellar insertion and has the VMO attached to it, and the nonoverlap region close to the femoral origin without the overlying VMO. 24 Anatomically, the total length of the MPFL was approximately 58.8 mm, of which 20.3 mm (35%) was in the overlap region and 38.5 mm (65%) was in the nonoverlap region. 27 Sallay et al reported 94% patients with patellar dislocations had an avulsion of MPFL in their study, while Sanders et al reported the rate of the MPFL injury was 100% in their series.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3): the overlap region, which is proximal to the patellar insertion and has the VMO attached to it, and the nonoverlap region close to the femoral origin without the overlying VMO. 24 Anatomically, the total length of the MPFL was approximately 58.8 mm, of which 20.3 mm (35%) was in the overlap region and 38.5 mm (65%) was in the nonoverlap region. 27 Sallay et al reported 94% patients with patellar dislocations had an avulsion of MPFL in their study, while Sanders et al reported the rate of the MPFL injury was 100% in their series.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the same midsubstance injury with or without the presence of a VMO attachment may result in different clinical outcomes. Kang et al 24 introduced a VMObased three-part classification for acute MPFL injuries that described the MPFL injuries in terms of their relationship with the VMO attachment: an overlap-region injury, a nonoverlapregion injury, and combined injuries. They reported that the outcomes of nonsurgical treatment are superior in the overlapregion injury than the nonoverlap region.…”
mentioning
confidence: 99%
“…The location of MPFL injury along its horizontal length is variable in the literature [6,8,20,22,29,40]. Data Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic exercise seems to play a primary role in each stage of recovery. At present, there is no evidence about the choice of exercises [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] .…”
Section: Rehabilitation Approachesmentioning
confidence: 99%